Increased sorbitol levels in the hypertrophic ligamentum flavum of diabetic patients with lumbar spinal canal stenosis. Issue 5 (11th April 2017) - Luo, Jiaquan; Huang, Lu; Chen, Zhuo; Zeng, Zhaoxun; Miyamoto, Takeshi; Wu, Hao; Zhang, Zhongzu; Pan, Zhimin; Fujita, Nobuyuki; Hikata, Tomohiro; Iwanami, Akio; Tsuji, Takashi; et al.
ABSTRACT: The pathomechanism of the ligamentum flavum (LF) hypertrophy in diabetic patients with lumbar spinal canal stenosis (LSCS) remains unclear. A cross‐sectional study was undertaken to investigate the mechanism of LF hypertrophy in these patients. Twenty‐four diabetic and 20 normoglycemic patients with LSCS were enrolled in the study. The structure of the LF in the study subjects was evaluated using histological and immunohistochemical methods, and the levels of sorbitol, pro‐inflammatory cytokines, and the fibrogenic factor, TGF‐β1, in the LF were analyzed. In vitro experiments were performed using NIH3T3 fibroblasts to evaluate the effect of high‐glucose conditions and an aldose reductase inhibitor on the cellular production of sorbitol, pro‐inflammatory factors, and TGF‐β1. We found that the LF of diabetic patients exhibited significantly higher levels of sorbitol and pro‐inflammatory cytokines, TGF‐β1 and of CD68‐positive staining than that of the normoglycemic subjects. The diabetic LF was significantly thicker than that of the controls, and showed evidence of degeneration. The high glucose‐cultured fibroblasts exhibited significantly higher levels of sorbitol, pro‐inflammatory factors, and TGF‐β1 compared to the low glucose‐cultured cells, and these levels were dose‐dependently reduced by treatment with the aldose reductase inhibitor. Taken together, our data suggests that increased sorbitol levels in the LF of diabetic patients results in increased production of pro‐inflammatory and fibrogenic factor, which contribute to LF hypertrophy, and could increase the susceptibility of diabetic patients to LSCS. Furthermore, aldose reductase inhibition effectively reduced the levels of sorbitol and sorbitol‐induced pro‐inflammatory factor expression in high glucose‐cultured fibroblasts. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:1058–1066, 2017.